The Meta VCI Map consortium for meta‐analyses on strategic lesion locations for vascular cognitive impairment using lesion‐symptom mapping: Design and multicenter pilot study. Issue 1 (12th April 2019) - Weaver, Nick A.; Zhao, Lei; Biesbroek, J. Matthijs; Kuijf, Hugo J.; Aben, Hugo P.; Bae, Hee‐Joon; Caballero, Miguel Á.A.; Chappell, Francesca M.; Chen, Christopher P.L.H.; Dichgans, Martin; Duering, Marco; Georgakis, Marios K.; et al.
Abstract: Introduction: The Meta VCI Map consortium performs meta‐analyses on strategic lesion locations for vascular cognitive impairment using lesion‐symptom mapping. Integration of data from different cohorts will increase sample sizes, to improve brain lesion coverage and support comprehensive lesion‐symptom mapping studies. Methods: Cohorts with available imaging on white matter hyperintensities or infarcts and cognitive testing were invited. We performed a pilot study to test the feasibility of multicenter data processing and analysis and determine the benefits to lesion coverage. Results: Forty‐seven groups have joined Meta VCI Map (stroke n = 7800 patients; memory clinic n = 4900; population‐based n = 14, 400). The pilot study (six ischemic stroke cohorts, n = 878) demonstrated feasibility of multicenter data integration (computed tomography/magnetic resonance imaging) and achieved marked improvement of lesion coverage. Discussion: Meta VCI Map will provide new insights into the relevance of vascular lesion location for cognitive dysfunction. After the successful pilot study, further projects are being prepared. Other investigators are welcome to join. Highlights: Lesion location is an important determinant of cognitive impact of vascular damage. Previous lesion‐symptom mapping studies had limited brain lesion coverage. Meta VCI Map provides a platform for multicenter lesion‐symptom mapping research. The pilot study shows that multicenter data integration is feasible and improves coverage. Multicenter studies enable comprehensive assessment of strategic lesion locations.